Konsep Pendidikan Halaqah 'Ala Nabi Muhammad SAW dan Relevansinya di Era Society 5.0 - Nurdiyanto, Nurdiyanto; Muslihah, Eneng; Suteja, Ade; Mubarok, Adha (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2024)
The halaqah method is a reminder of the development of current education patterns. This research aims to analyze and examine in depth what is the concept of halaqah education ala Rasulullah SAW? and what is the relevance of halaqah education in the era of society 5.0 as well as the challenges and obstacles to the halaqah education model in the era of society 5.0. The approach taken in this research uses a qualitative approach with the library research method. Data sources in this research include journal articles, e-books, online proceedings, magazines, newspapers, and other internet media. Data collection techniques include collecting literature sources and then classifying and presenting the data to conclusions. So, the analysis technique used is the descriptive analysis technique. The results of the research contain several findings such as the history of halaqah education, introduction to the concept of halaqah education, definition and basic concepts of education, relevance of halaqah education to the teachings of the Prophet Muhammad SAW, uniqueness of halaqah education in Islam, halaqah education in the era of Society 5.0, challenges and analysis of challenges and opportunities for halaqah education in the era of society 5.0. This research concludes that the existence of the halaqah method ala Rasulullah SAW needs to be harmonized with developments in technology and information, especially in the nuances of education, so that this method is a way to facilitate the delivery of scientific teachings, both those based on foundations (Islam) and those that support or forum. science in general.